Quercetin ameliorates ox-LDL-induced cellular senescence of aortic endothelial cells and macrophages by p16/p21, p53/SERPINE1, and AMPK/mTOR pathways - Liang, Xiao; Zhang, Jingyuan; Yu, Jiangbo; Zhao, Jiyi; Yang, Shusen (European journal of medical research, 2025)
Atherosclerosis (AS), a chronic inflammatory disease of the arterial wall, remains a dominant cause of death and disability globally. Quercetin has been evidenced to be effective against AS, but the exact mechanisms are still largely unclear.
Gesehen am 02.06.2025